Training in Improving The Quality of Communication Using the Communication Patterns of Adolescent Students of Al-Mu'awwanah Mosque - Aziz, Abdul; Idawati, Idawati (Universitas Islam Negeri Alauddin Makassar, 2020)
This community service activity aims to provide Quality Communication Training by Using the Communication Pattern of Youth Groups of Almu'awwanah Mosque. This activity was held for one full day, starting at 8:00 to 16:00 WIB. The material provided was in the form of communication quality training using communication patterns of youth groups of the Al-Mu'awwanah mosque. The total number of participants as many as 50 youth. The majority of whom came from members of the Al-Muawwanah mosque, and by adolescents in the Yellow Bamboo Village. The service activities provided result in 1) Being able to improve the quality of communication, 2) Adding experience in group communication patterns to strengthen group communication relationships for youth and Youth Al-Mu'awwanah Mosque, 3) Having quality communication within and fellow group members, 4) Creating close friendships in groups, 5) Able to run the youth program well according to the purpose, 6) Able to realize the mosque management program and the most important of these community service activities is being able to reactivate mosque teenagers.